Implementasi Penugasan Dosen di Sekolah (PDS) dalam Mata Kuliah Strategi, Metode, dan Media Pembelajaran Berbasis Lesson Study - Dewi Ratnaningsih (Edukasi Lingua Sastra, 2020)
After undergoing stage 1 PDS program, namely the implementation of lecturers to become "teachers" in schools, the next stage is the implementation of PDS within the university environment. The implementation of the PDS program phase 2 is realized in the Strategy, Method and Learning Media courses. The implementation of the PDS program in tertiary institutions is based on the principle of lesson study. Based on the results of the application, there are a number of lesson learns obtained. Lesson learns include: 1) giving material with appropriate learning media becomes a special attraction for students, 2) the formation of learning groups allows students to develop collaborative and communicative abilities, 3) assignments in the form of videos in the application of collaborative learning methods make students learn directly so a more maximal understanding process is obtained.